2017
DOI: 10.1080/00325481.2018.1410054
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of depression and anxiety among subjects with metabolic syndrome and known type 2 diabetes mellitus – a population-based study

Abstract: In conclusion, depressiveness and anxiety were associated positively with age and female gender and were more prevalent among subjects with MetS and known diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…It is acknowledged that T2DM may incite distress, as patients suffer with a need to self-manage such chronic disease, recurrently detect blood glucose levels, and show adequate compliance adherence (Marshall et al, 1997;Marchini et al, 2018), which facilitate the avoidance of unhealthy behavior and outcomes. It is also known that people with psychopathological features showed an amplified risk to develop T2DM onset at a 10-year follow-up, independently from conventional risk factors for DM (Engum, 2007;Shinkov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that T2DM may incite distress, as patients suffer with a need to self-manage such chronic disease, recurrently detect blood glucose levels, and show adequate compliance adherence (Marshall et al, 1997;Marchini et al, 2018), which facilitate the avoidance of unhealthy behavior and outcomes. It is also known that people with psychopathological features showed an amplified risk to develop T2DM onset at a 10-year follow-up, independently from conventional risk factors for DM (Engum, 2007;Shinkov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and fear-related disorders include generalized anxiety disorder (GAD), panic disorder, agoraphobias, specific phobias, social anxiety disorder, associated or not with panic attacks [1,2], and are collectively ranked the sixth most important contributor of non-fatal negative health outcomes [2]. Anxiety is highly prevalent in patients suffering with co-occurring medical conditions, including metabolic syndrome and diabetes [3], cancer [4], HIV infection [5], and several other conditions. Anxiety is also highly prevalent in the general population: a study investigating subthreshold anxiety disorder in the general Dutch population has found a prevalence of 11.4% [6], whilst another study investigating self-evaluated anxiety in the general Norwegian population found that 6.6% of respondents reported current anxiety, and 21.7% of them reported lifetime anxiety [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is a cluster of interconnected physiological, biochemical and clinical factors that is associated with cardiovascular disease (CVD) and type II diabetes mellitus (DM) risk 3. MetS has been associated with depression,4 cancer,5 health-related quality of life6 and all-cause mortality 7. MetS has five primarily components—central obesity, elevated triglycerides, hypertension, low high-density lipoprotein cholesterol (HDL-C) and elevated fasting glucose.…”
Section: Introductionmentioning
confidence: 99%